Pengujian Aplikasi E-learning Berbasis Web Di SMP Excellent 1 Tangerang - Dendi; Arya Kurniasndi; Muhammad Jukahpin; Fahmi Miftakhul Fuadi; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
So far, the learning process at SMP EXCELLENT 1 is still conventional, in other words that a teaching and learning process between students and teachers can only be carried out on the condition that there are meetings between students and teachers in the classroom. If the meeting between students and teachers does not occur or the teacher in question is not present and learning time is limited by the school, then indirectly the learning process will be hampered. Various new concepts and techniques in teaching have been developed to replace traditional methods which only rely on a one-way teaching method in the classroom. One of the teaching methods that is currently being developed in the present is e-learning. E-learning can help teachers distribute their various teaching materials without having to be in class using the internet, this can maximize the limited learning time in class. The development of technology is currently growing very rapidly and all human activities depend on the sophistication of technology. Some schools and courses have partly used E-Learning in the teaching and learning process. SMP Excellent 1 has a computer laboratory with internet access but does not have supporting facilities such as E-Learning.